(untitled) (Journal of Parents and Teachers, 2025)
This article explores the early stages of writing in childhood. Writing is a process, and as such, it requires time, trial, and practice. Learning to write involves a journey where making mistakes and practicing are essential. However, these mistakes can become ingrained over time if we overlook certain prerequisites, the emotional component underlying the process, and the crucial role of play as a driving force in children’s lives.